FuzzyStudio: A web tool for modeling and simulation of fuzzy systems - De Soto A.R. (2014)
© 2014 IEEE.The study of Fuzzy Logic in higher education is hampered by the limited time devoted to it, since it is frequently embedded into a discipline along with other topics. In spite of their potential for application in several areas of knowledge, such as education, administration and engineering, teaching Fuzzy Logic is also restricted by the absence of an environment to easily develop fuzzy systems. This work deals with the development of a tool for modelling and simulating fuzzy systems. The tool aims to facilitate the fuzzy systems building process. As an important feature, an execution environment to the model has been developed. This feature improves graphical execution, FCL standard code generation and Java code generation. Furthermore, the tool enables collaborative work, allowing that more than one user simultaneously work on the same project. By now, tool supports Mamdani-type fuzzy systems and its implementation is exploited with the jFuzzyLogic library. The tool was used in a class of Artificial Intelligence in the Santa Catarina State University. In the opportunity, the students performed exercises on the platform and also delivered a work proposed by the professor. After that it was conducted a survey with those students in order to evaluate the facility of using the software. The system showed to be efficient and simple for the construction of fuzzy systems as well as for the simulation and generation of fuzzy artifacts. So, it can be applied in an academic environment to practice fuzzy theories, as well as in the commercial context, in the construction of intelligent solutions that use Fuzzy Logic.